2016
DOI: 10.1111/dom.12753
|View full text |Cite
|
Sign up to set email alerts
|

Reduced peripheral activity leading to hepato‐preferential action of basal insulin peglispro compared with insulin glargine in patients with type 1 diabetes

Abstract: Aims: Basal insulin peglispro (BIL), a novel PEGylated basal insulin with a large hydrodynamic size, has a delayed absorption and reduced clearance that prolongs the duration of action. The current study compared the effects of BIL and insulin glargine (GL) on endogenous glucose production (EGP), glucose disposal rate (GDR) and lipolysis in patients with type 1 diabetes. Portions of this study were presented as abstracts at the 75th Scientific Sessions of the American Diabetes Association, Materials and Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
(98 reference statements)
2
19
0
Order By: Relevance
“…Although conventional insulins suppress lipolysis, insulin clamp studies show that BIL suppresses lipolysis to a lesser degree than human insulin in dogs and compared to glargine in patients with T1D . Similar results were reported with the hepatopreferential insulin‐327 .…”
Section: Discussionsupporting
confidence: 73%
“…Although conventional insulins suppress lipolysis, insulin clamp studies show that BIL suppresses lipolysis to a lesser degree than human insulin in dogs and compared to glargine in patients with T1D . Similar results were reported with the hepatopreferential insulin‐327 .…”
Section: Discussionsupporting
confidence: 73%
“…Weight gain is commonly associated with insulin treatment, and previous studies have identified weight gain following GL treatment, but weight loss in T1DM patients treated with BIL . This difference may reflect the fact that BIL has attenuated peripheral effects compared to GL, resulting in a hepato‐preferential action . In Phase 3 studies, BIL, but not GL, increased triglycerides in T1DM patients, which may reflect less suppression of lipolysis by BIL in peripheral adipose tissue .…”
Section: Discussionsupporting
confidence: 93%
“…Increases in both K-18 and ALT with BIL were greater in previously insulin-treated patients with T2D in whom statistically significant increases in LFC (~5%) were observed 7 32. As previously reported,7 higher LFC with BIL versus glargine treatment may reflect the fact that BIL suppresses lipolysis to a lesser degree than glargine 44. Switching from an insulin that potently suppresses lipolysis (glargine) to one with a weaker effect on lipolysis (BIL) may result in increased flux of FFA to the liver that are esterified into hepatic triglyceride.…”
Section: Discussionmentioning
confidence: 67%